2022
DOI: 10.1111/jomf.12862
|View full text |Cite
|
Sign up to set email alerts
|

Childhood exposure to family violence and adult sibling relationships

Abstract: This study investigated how experiencing childhood family violence can affect aspects of adult sibling relationships. Background: Established evidence shows the long-term effects of childhood adversity on several domains of adult lives. Few studies, however, have examined the impact that childhood family violence exposure has on sibling relationships later in adulthood. To address this gap, this study examined the latent class structure of childhood exposure to family violence. We also investigated whether and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Specifically, there was a significant difference at the initial assessment between those with a history of maltreatment and those without such a history. This finding is consistent with prior studies that have demonstrated the long reach of childhood maltreatment on relationships with families of origin (Kong, 2018a; Kong & Goldberg, 2022; Savla et al, 2013). It also supports the congruence hypothesis, which posits that dysfunctional parent–child relationships can influence the patterns and dynamics of sibling relationships (Derkman et al, 2011; Hank & Steinbach, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, there was a significant difference at the initial assessment between those with a history of maltreatment and those without such a history. This finding is consistent with prior studies that have demonstrated the long reach of childhood maltreatment on relationships with families of origin (Kong, 2018a; Kong & Goldberg, 2022; Savla et al, 2013). It also supports the congruence hypothesis, which posits that dysfunctional parent–child relationships can influence the patterns and dynamics of sibling relationships (Derkman et al, 2011; Hank & Steinbach, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Relatedly, our main focus was on examining the lasting impact of childhood maltreatment without considering the exposure to other childhood adversities, such as sibling violence. Sibling abuse may occur in conflict-ridden families involving child maltreatment (Kong & Goldberg, 2022), suggesting the potential direct negative impact of sibling abuse victimization on adult sibling relationship quality. Although the analytic models are robust, we cannot rule out the potential bias associated with unmeasured confounders, such as adverse life events during adulthood.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations